Penggarapan Ulang Ilustrasi Musik Film “Jendela” Karya Randi Pratama; Studi Karya Tugas Akhir Larasati Rahma Aditiara - Rosiana Dewi, Maria Octavia (Resital: Jurnal Seni Pertunjukan, 2022)
This research aims to examine the basic idea of Larasati Rahma Aditiara in the re-create of the music illustration of the film "Jendela" by Randi Pratama and the stages and creative processes in it. The "Jendela" is a family drama movie that tells the story of a less harmonious father and son relationship. The relationship eventually improved, and communication returned harmoniously. The methods in this study are qualitative with an interpretive descriptive approach based on film music theory. The result of this study is the desire of Larasati Rahma Aditiara to interpret the meaning and emotions contained in the film "Jendela" by reworking the film's musical illustrations to be conveyed directly to the audience. The desire becomes the basis of the idea in work. The concept of this work uses leitmotif development and efforts to place musical idioms of Javanese tradition. There are stages of making work, namely the determination of the film music genre, the determination of films and workflows. The composer performs five workflows under the direction of the director. The work has seven cue sections of musical illustration, with a brief introduction. The finale part is played in the credit title at the end of the film.